Pemberdayaan UMKM dalam Peningkatan Produksi dan Distribusi Pangan Lokal melalui Penerapan Digital Marketing - Mochammad Syafiuddin Shobirin; Ach Saifullah; Nurul Indana; Syarifatul Mubariroh; Ikbal Kresno Tyo Prayoga (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Cupak Village, located in the Ngusikan District, Jombang Regency, has significant potential in local food production. However, the main challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in this area are limited market access and conventional marketing methods. This community service program is designed to empower MSMEs in Cupak Village by implementing digital marketing strategies to increase production capacity and expand the distribution of local food products. Through ongoing training and mentoring, MSMEs will be equipped with the skills to utilize various digital platforms, such as social media, e-commerce, and content marketing, which are expected to significantly broaden their market reach. The steps in this program include several phases: 1) identifying the needs and challenges MSMEs face in terms of marketing, 2) providing basic training on digital marketing concepts, 3) offering technical assistance in creating marketing content and using digital platforms, and 4) evaluating the impact of digital marketing on increasing production and distribution. With the optimization of technology, this program is expected to enhance the local competitiveness of MSMEs while promoting economic growth in the village. The expected outcomes of this program include improving the knowledge and skills of MSME actors in digital marketing, which will ultimately contribute to increased sales and distribution of local food products. Additionally, the implementation of digital marketing is also expected to open up new market opportunities beyond Cupak Village, which in turn can improve the overall welfare of the local community.